Bibliometric analysis for working capital: Identifying gaps, co-authorships and insights from a literature survey - Vítor Jo\~ao Pereira Domingues Martinho (International Journal of Financial Studies, 2021)
From a financial perspective, working capital represents the liquidity of firms that makes them able to deal with short-term liabilities in current assets (inventories, receivables accounts, and net financial resources). However, this concept is also considered in scientific literature as, among other meanings, stock of productive capital, or variables costs. Considering the importance of working capital in a firms' dynamics, the principal objective of this study is to highlight the main gaps and insights in literature concerning working capital and to suggest future research. For this purpose, bibliometric analysis was carried out through bibliographic information from both the Web of Science Core Collection and from the Scopus for the topic of "working capital". These data were first worked through bibliometric approaches, considering the VOSviewer and Gephi software and later surveyed through a literature review. As the main insights, it is worth highlighting that there are several gaps in related literature, where the most worrying is the weak reference to sustainability or sustainable development concepts. Finally, the majority of the networked research was focused on just a few authors, organizations, and countries.
Keywords: 330; benchmarking; centrality; financial studies; Gephi; literature review; Scopus; VOSviewer; Web of Science